2014
DOI: 10.1007/s12013-014-0149-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects and Mechanism of miR-92a and miR-126 on Myocardial Apoptosis in Mouse Ischemia-Reperfusion Model

Abstract: Our objective was to explore the effects of miR-92a and miR-126 on myocardial apoptosis in mouse ischemia-reperfusion model and further investigate the underlying mechanisms. Eighteen Kunming mice were selected and randomly divided into sham operation group and ischemia-reperfusion group with nine mice in each group. Cardiac muscle tissue was stained with Evans blue to confirm myocardial infarction and ischemia. Annexin V/PI double staining was used to detect the apoptotic rate of myocardial cells, and termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Jiang and colleagues (Jiang et al, 2014), however, suggested recently that miR-126 may participate in myocardial cell apoptosis via heat shock protein 70. The target genes of miR-126 were not confirmed in this study and require further investigation to allow for the exact mechanism of miR-126 in the regulation of myocardial cell apoptosis to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang and colleagues (Jiang et al, 2014), however, suggested recently that miR-126 may participate in myocardial cell apoptosis via heat shock protein 70. The target genes of miR-126 were not confirmed in this study and require further investigation to allow for the exact mechanism of miR-126 in the regulation of myocardial cell apoptosis to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation‐related targets of miR‐146a include IL‐1 receptor‐associated kinase‐1 (IRAK1), TNF receptor‐associated factor 6 (TRAF6), and IL‐1ÎČ. MiR‐126 regulates the expression of vascular adhesion molecules and is implicated in ER stress expression as it can modulate the heat stress protein Hsp70 …”
Section: Introductionmentioning
confidence: 99%
“…MiR-126 regulates the expression of vascular adhesion molecules and is implicated in ER stress expression as it can modulate the heat stress protein Hsp70. 18 In this study, we investigated the effects of maternally administered melatonin on LPS-induced brain cellular stress. We report here that maternal lipopolysaccharide (LPS) sensitizes the immature rat brain to a second postnatal excitotoxic injury.…”
mentioning
confidence: 99%
“…Our previous studies showed that long-term intermittent hypoxia could result in eccentric cardiac hypertrophy in rats (Chen et al, 2007) and induce both mitochondrial-dependent apoptotic and Fas death receptor-dependent apoptotic pathways in rat hearts (Lee et al, 2007). Results from several studies suggested that cardiomyocyte apoptosis is a critical factor in the initiation and progression of many types of cardiac disease (Konstantinidis et al, 2012) such as ischemia/reperfused heart MI and end-stage heart failure (Jiang et al, 2014;Lim et al, 2014;Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%